Each month Allison gets a $15 allowance and earns $100 working at the theater. She uses the expression 15x+100y to keep track of her earnings Part A Part B Part C

Answers

Answer 1
Answer:

Step-by-step explanation:

The expression for he earning of Allison and her allowance is as follows :

15x+100y

Part A

Variables are x and y. Coefficients are 15 and 100.

Part (B)

There are two terms in this expression. + is used to separate the terms. 15x and 100y are the terms.

Part (C) As $15 shows her earning from allowances. Hence, 15x shows allowance.


Related Questions

Which is a recursive formula for the sequence 99.4, 0, –99.4, –198.8, where f(1) = 99.4?
Laura is thinking of a number such that the sum of the number and five times two more than the number is 26 more than four times the number. Determine the number Laura is thinking of.
If a ship's path is mapped on a coordinate grid, it follows a straight-line path of slope 5 and passes through point (2, 3)Part A: What is the equation of the path? Part B: Does the ship pass through point (6, 25)? Part C: A second ship follows a straight line, with the equation x + 5y − 15 = 0. Are these two ships sailing perpendicular to each other? Justify your answer.
Justin ate 3/5 of a box of raisins.His sister then ate of the 1/4 of the raisins left in the box. What fraction of thebox of raisins did Justin's sister eat?​
including the end zone a football field measure 120 yds long by 53 1/3 yards wide. what is the area of the football field ?

An arithmetic sequence is given below.-4, -10, -16, -22, ...
write an explicit formula for the Nth term aN.

Answers

Answer:

an​=−6n+2

Step-by-step explanation:

First, you need to identify the first term and the common difference of the sequence. The first term is the value of the first element, which is -4. The common difference is the amount that is added or subtracted to each term to get the next one, which is -6 in this case. You can find it by subtracting any two consecutive terms, such as -10 - (-4) = -6 or -16 - (-10) = -6.

Next, you need to use the standard explicit formula for an arithmetic sequence, which is:

an​=a1​+d(n−1)

where an​ is the Nth term, a1​ is the first term, d is the common difference, and n is any term number.

Finally, you need to substitute the values of a1​ and d that you found in the first step into the formula. This gives:

an​=−4+(−6)(n−1)

This is the explicit formula for the Nth term aN of the given arithmetic sequence. You can simplify it further by expanding and combining like terms:

an​=−4−6n+6

an​=−6n+2

The time, in seconds, that it takes a pendulum to swing back and forth is modeled by the equation below. f (l) = 2 pi StartRoot StartFraction l Over 32 EndFraction EndRoot, where l is the length of the pendulum in feet What is the approximate length of a pendulum that takes 2.4 pi seconds to swing back and forth?

Answers

Answer:

46.08 feet.

Step-by-step explanation:

Given that, for length, l feet, the time period, f(l), of the pendulum is

f(l)=2\pi\sqrt{(l)/(32)}.

As the time period equals the time taken by the pendulum in one back and forth motion, so, actually, the given 2.4\pi seconds to swing back and forth is the time period.

Let l_0 feet be the length of the pendulum for the time period 2.4\pi seconds, so

f(l_0)=2.4\pi

\Rightarrow 2\pi\sqrt{(l_0)/(32)}=2.4\pi

\Rightarrow \sqrt{(l_))/(32)}=1.2

\Rightarrow (l_0)/(32)=(1.2)^2 [squaring on both the sides]

\Rightarrow l_0=1.44*32

\Rightarrow l_0=46.08

Hence, the approximate length of a pendulum that takes 2.4 \pi seconds to swing back and forth is 46.08 feet.

Answer:

the answer is d on edge 2020

Step-by-step explanation:

Help me please!! asap!

Answers

The equation represent the situation is:

First let x be number of small apartment

Since the total apartment is 18

Then number of large apartment is 18 – x

So the equation is:

17,600 = 800x + 1200(18-x)

Simplifying

17,600 = 800x + 21,600 – 1200x

400x = 4000

X = 10

What is the inverse of the function y = 4x + 5?

Answers

The inverse of the function y = 4x + 5 is f^(-1)(x) = (x-5)/(4)

The given function is:

y = 4x  +  5

To find the inverse of the given function y = 4x  +  5, follow the following steps:

Make x the subject of the formula:

y = 4x  +  5\n\n4x = y - 5\n\nx = (y)/(4)-(5)/(4)

Replace x by f^(-1)(x) and replace y by x.

The resulting function represents the inverse of the function y = 4x  +  5

f^(-1)(x)=(x)/(4)-(5)/(4)

Which can be further simplified as:

f^(-1)(x) = (x-5)/(4)

The inverse of the function y = 4x + 5 is f^(-1)(x) = (x-5)/(4)

Learn more here: brainly.com/question/12220962

Answer:

y = 1/4 x - 5/4

Step-by-step explanation:

y = 4x + 5

Switch x and y.

x = 4y + 5

Solve for y.

4y = x - 5

y = 1/4 x - 5/4

Identify the direction of rotation that maps triangle BCD to triangle B’C’D’.The triangle is rotated in a
direction-----

Answers

The triangle is rotated in a clockwise direction, as per the given conditions.

What is the triangle?

The triangle is a geometric shape that includes 3 sides and the sum of the interior angle should not be greater than 180°

Here,
It seems to be questioned is incomplete, we assume that the direction of rotation that maps triangle BCD to triangle B’C’D’ on a coordinate plane from quadrant 2 to quadrant 1 is about the origin. As rotation from quadrat 2 to one about origin represents the clockwise direction.

Thus, the triangle is rotated in a clockwise direction, as per the given conditions.

Learn more about triangles here:
brainly.com/question/2773823

#SPJ6


Answer:

clockwise

Step-by-step explanation:

Which statement is true?

Answers

Answer:

There is no statement here, please check what you posted again

Answer:

Step-by-step explanation:

I Dont See Anything